Making sense of the comprehensive assessment - Viral V. Acharya; Sascha Steffen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
The European Central Bank (ECB) has finalized its comprehensive assessment of the solvency of the largest banks in the euro area and on October 26 disclosed the results of this assessment. In the present paper, Acharya and Steffen compare the outcomes of the ECB's assessment to their own benchmark stress tests conducted for 39 publically listed financial institutions that are also included in the ECB's regulatory review. The authors identify a negative correlation between their benchmark estimates for capital shortfalls and the regulatory capital shortfall, but a positive correlation between their benchmark estimates for losses under stress both in the banking book and in the trading book. They conclude that the regulatory stress test outcomes are potentially heavily affected by discretion of national regulators in measuring what is capital, and especially the use of risk-weighted assets in calculating the prudential capital requirement.
urn:nbn:de:hebis:30:3-350190
Keywords: 330; Asset Quality Review; Single Supervisy Mechanism; European Central Bankor